2017
DOI: 10.1155/2017/5987082
|View full text |Cite
|
Sign up to set email alerts
|

Omega‐3 Polyunsaturated Fatty Acids in Critical Illness: Anti‐Inflammatory, Proresolving, or Both?

Abstract: Prognosis and outcomes of critically ill patients are strictly related with inflammatory status. Inflammation involves a multitude of interactions between different cell types and chemical mediators. Omega-3 polyunsaturated fatty acids (PUFAs), mainly represented by eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), are able to inhibit different pathways including leukocyte chemotaxis, adhesion molecule expression and interactions, and production of inflammatory cytokines, through the action of specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(59 citation statements)
references
References 39 publications
0
51
0
4
Order By: Relevance
“…Positive correlation with synovial fluid composition and inversed correlation with pain score [291] ↓ Incidence and improved prognosis [292][293][294][295][296] ↓ Duration of morning stiffness and ↓ number of tender and swollen joints [297] Polymyositis and Dermatomyositis ↑ Skeletal muscle growth and functions [298] Sjögren Syndrome ↓ Inflammation and ↑ barrier function in the salivary glands [299,300] Systemic Lupus Erythematosus ↓ Inflammatory mediators, leukocyte chemotaxis and adhesion molecules expression [301] Antiphospholipid Syndrome ↑ Endothelial function [302] Multiple Sclerosis ↑ M2-like macrophages shift, prevented de-myelinization, promoted neuroprotection and re-myelinization ↓ incidence [303][304][305][306] Type 1 Diabetes Protection against T1DM in infants, no protective effect in older children reported [307,308]…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Positive correlation with synovial fluid composition and inversed correlation with pain score [291] ↓ Incidence and improved prognosis [292][293][294][295][296] ↓ Duration of morning stiffness and ↓ number of tender and swollen joints [297] Polymyositis and Dermatomyositis ↑ Skeletal muscle growth and functions [298] Sjögren Syndrome ↓ Inflammation and ↑ barrier function in the salivary glands [299,300] Systemic Lupus Erythematosus ↓ Inflammatory mediators, leukocyte chemotaxis and adhesion molecules expression [301] Antiphospholipid Syndrome ↑ Endothelial function [302] Multiple Sclerosis ↑ M2-like macrophages shift, prevented de-myelinization, promoted neuroprotection and re-myelinization ↓ incidence [303][304][305][306] Type 1 Diabetes Protection against T1DM in infants, no protective effect in older children reported [307,308]…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…Systemic lupus erythematosus (SLE) is a prototype of autoimmune diseases with no clear etiology. N-3 PUFAs have a positive impact on clinical conditions in SLE by reducing inflammatory mediators, the chemotaxis of leukocytes, and the expression of adhesion molecules [301]. A 16-week randomized controlled trial has established that n-3 PUFA supplementation improves endothelial function also in patients with an antiphospholipid syndrome characterized by endothelial dysfunction and recurrent thrombotic episodes [302] (Table 3).…”
Section: Rheumatic Diseasesmentioning
confidence: 99%
“…Omega-3 PUFAs inhibit leukocyte chemotaxis, adhesion molecule expression and production of inflammatory cytokines, through the action of specialized pro-resolving mediators, such as lipoxins, resolvins, protectins, and maresins, which reduce inflammation (23). Eicosapentaenoic acid and docosahexaenoic acid, omega-3 fatty acids found in oily fish, are able to partly inhibit inflammation, but further clinical trials are required to see their effects on SLE.…”
Section: Dietary Factorsmentioning
confidence: 99%
“…Commensurate with these descriptions, there are several mechanisms related to the therapeutic effects of DHA on apoptosis and multiple physiological roles [11]. It has been shown that DHA and other n-3 polyunsaturated fatty acids could affect the production of different cytokines that coincided with simultaneous synthesis in ammation resolving metabolites such as maresins, resolvins, and protectins [12,13]. DHA increases the bioactivity of sensory molecules such as peroxisome proliferator-activated receptors and NF-B by which control the biosynthesis of other cytokines.…”
Section: Discussionmentioning
confidence: 98%